2017
DOI: 10.1039/c7ra06126a
|View full text |Cite
|
Sign up to set email alerts
|

Inserting AgCl@rGO into graphene hydrogel 3D structure: synergy of adsorption and photocatalysis for efficient removal of bisphenol A

Abstract: An AgCl@graphene (rGO) core–shell structure was fabricated and then loaded into reduced graphene oxide hydrogel (rGH) to form AgCl@rGO-rGH by the chemical reduction method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, there are rare reports on such a high removal efficiency and long-term stability of aerogel-based photocatalysts in a continuous photodegradation system (Figure a, Table ). , The better photocatalytic performance of the SGAMs is attributed to the advantages of Ag 3 PO 4 and its association with honeycomb-shaped GO aerogel microspheres. First, numerous ice crystals induce the formation of a honeycomb-like structure with channels radially diverging from the center, which shortens the diffusion pathway of pollutants and allows to achieve rapid adsorption equilibrium; second, the interaction between Ag 3 PO 4 nanoparticles and the GO matrix facilitates fast electron hopping from Ag 3 PO 4 to the GO sheets, which significantly reduces the photocorrosion of Ag 3 PO 4 and enhances the photocatalytic activity of Ag 3 PO 4 (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, there are rare reports on such a high removal efficiency and long-term stability of aerogel-based photocatalysts in a continuous photodegradation system (Figure a, Table ). , The better photocatalytic performance of the SGAMs is attributed to the advantages of Ag 3 PO 4 and its association with honeycomb-shaped GO aerogel microspheres. First, numerous ice crystals induce the formation of a honeycomb-like structure with channels radially diverging from the center, which shortens the diffusion pathway of pollutants and allows to achieve rapid adsorption equilibrium; second, the interaction between Ag 3 PO 4 nanoparticles and the GO matrix facilitates fast electron hopping from Ag 3 PO 4 to the GO sheets, which significantly reduces the photocorrosion of Ag 3 PO 4 and enhances the photocatalytic activity of Ag 3 PO 4 (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, photocatalysis breaks down organic contaminants to their nontoxic components with the aid of a semiconductor harvesting solar light Table contains some of the available literature wherein semiconductor composites are employed for water treatment through a adsorption–photocatalysis synergistic approach. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that AgCl can exhibit better stability by coupling them with graphene. For example, Chen et al had successfully fabricated AgCl@rGO‐rGH by compositing the graphene hydrogels with AgCl via a chemical reduction method, the photocatalytic activity and stability of the AgCl nanoparticles were improved remarkably after the introduction of rGO. Luo et al had fabricated the Ag/AgCl/rGO heterostructured photocatalyst by a mild oxidization reaction of hydrothermally prepared Ag/rGO in FeCl 3 solution, which displayed improved photocatalytic activity and stability than that of bare AgCl.…”
Section: Introductionmentioning
confidence: 99%